Indonesian Creative Economy 2025: Creative Industries MSMEs Competitiveness Strategy Towards International Markets Through Soar Analysis - Muhammad Syah Budi; Sri Ramadhani; Elida Elfi Barus (Journal of Indonesian Applied Economics, 2023)
Purpose This research aims to formulate a Creative Industries Development Strategy towards the International market as an economic driver in Indonesia. Design/methodology/approach This paper is carried out with a qualitative approach through the SOAR method, which is a strategic planning method used to evaluate strengths, opportunities, aspirations and results in the development of creative industries in Indonesia. Findings The result shows that producing the start-up S-A is a strategy obtained between Strengths (strengths) and Apirations (aspirations). Research limitations/implications                                               The limitation of this study is the use of SOAR analysis which only focuses on evaluate strengths, opportunities, aspirations and results rather than weaknesses or threats. Originality/value This study analyzes the strengthening of the Creative Industry Sector Market in Facing Creative Economy 2019-2025.